Historical perspective—weaving the lives of Florence Nightingale and Florence Nightingale David into the statistics classroom. (22nd April 2016) - Tunstall, Samuel Luke
Summary: This paper describes an activity to celebrate the lives of Florence Nightingale and Florence Nightingale David in statistics classrooms.